[68Ga]/[188Re] Complexed [CDTMP] Trans-1,2-Cyclohexyldinitrilotetraphosphonic Acid As a Theranostic Agent for Skeletal Metastases - Jaswal, Ambika P.; Meena, Virendra K.; Prakash, Surbhi; Pandey, Ankita; Singh, Baljinder; Mishra, Anil K.; Hazari, Puja P. (Frontiers in Medicine, 2017)
Objective Metastasis of the osseous tissue is one of the frequent and severe aggravations as a result of several neoplastic conditions, such as metabolic disorders, infections, and cancer. The objective of this study was to evaluate the pertinence of [68Ga]-trans-1,2-cyclohexyldinitrilo tetramethylene phosphonic acid (CDTMP) as a potential bone imaging agent for positron emission tomography (PET) applications as well as to assess [188Re]-CDTMP for bone pain palliation in metastatic skeletal disorders. Methods 68Ga complex of CDTMP was prepared at 80°C at pH 3.5, and 188Re complex of CDTMP was prepared at room temperature. [68Ga]-CDTMP complex was investigated as PET tracer while the therapeutic efficacy was assessed for [188Re]-CDTMP. Labeling efficiency, biodistribution, myelotoxicity, and imaging studies were carried out for the complexes synthesized. Both PET and MicroPET imaging studies were performed for [68Ga]-CDTMP whereas SPECT acquisitions were acquired for [188Re]-CDTMP. Data were analyzed semiquantitatively for all the scintigraphic scans obtained. Results The radiolabeling efficiency was observed to be >70% for [68Ga]-CDTMP. High bone uptake of [68Ga]-CDTMP as compared to contralateral tissue was found in PET imaging in Balb/C mice and New Zealand rabbit; the similar result for bone uptake was correlated in the biodistribution study of the compound in BALB/c mice at different time intervals. Biodistribution experiments carried out in mice showed maximum uptake of 6.12 ± 1.22%ID/g at 45 min postinjection. For [188Re]-CDTMP, total skeletal uptake was 8.12 ± 1.11%ID/g observed at 1 h postinjection from biodistribution data. High renal uptake confirms renal route of excretion. A good hydroxyapatite binding too was seen for both the complexes. No evidence of destruction or adverse functioning of vital organs was observed for the 188Re complex. Conclusion [68Ga]-CDTMP complex can be used as a promising PET bone imaging agent and [188Re]-CDTMP as a surrogate moiety for therapeutic application. Owing to the short half-life of 68Ga (68 min), cyclotron-independent radiopharmacy, fast clearance, and rapid renal excretion as evidenced in preclinical animal models. Very low myelotoxicity and highly selective bone uptake prove the potential of [188Re]-CDTMP for therapeutic application.